The Amsterdam connection - Leather, Sue (Cambridge English readers. Level 4, 2001)
Reporter Kate Jensen travels to Amsterdam when a friend is found dead there. Her search for the murderer takes her to parts of the city that tourists never see, and to a man prepared to kill to hide the truth. Kate soon discovers that football can be a very dangerous game.